The Influence of E-Service Quality, Product Authenticity, and Delivery Speed on Consumer Satisfaction in TikTok Shop - Seni Amelia Laode Saniharu; Sarifuddin T.; Nasrulhak Akkas (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to determine the influence of E-Service Quality, product authenticity, and delivery speed on consumer satisfaction at TikTok Shop. This research used a quantitative approach involving 180 students from the Faculty of Economics and Business at Universitas Muhammadiyah Palu as respondents, selected through purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the study indicate that E-Service Quality does not have a significant effect on consumer satisfaction, while product authenticity and delivery speed have a positive and significant effect on consumer satisfaction. Simultaneously, the three variables significantly influence consumer satisfaction, with product authenticity being the most dominant factor.